Health promoting lifestyles of Jordanian university students - Alkhawaldeh, Omar (International Journal of Advanced Nursing Studies, 2014)
Background: Health-promoting lifestyles of university students are strongly related to their current and subsequent health status. Low rates of health-promoting lifestyles among university students are still reported in literature. However, few studies in Jordan have examined health-promoting behaviors among university students. Objectives: This study was aimed to assess health-promoting lifestyles among university students and to examine relationship between the university student's characteristics and health-promoting lifestyles. Methods: A cross-sectional, correlational design was conducted using a sample of university students at Mutah University in Jordan. The Health Promotion Lifestyle Profile II (HPLP-II) scale was given to students as self-administered questionnaire. Data were analyzed by descriptive and inferential statistics. Results: Of the 480 distributed questionnaires; 340 completed questionnaires were returned. Results revealed that the total average score for the HPLP-II for students was 2.4 (SD =0.4). The highest mean score was for spiritual growth subscale (M=3.0, SD= 0.7) and the lowest mean score was for physical activity subscale (M = 2.0, SD = 0.7). Students' scores on the health responsibility, nutritional habits, spiritual growth, interpersonal relations, and stress-management subscales of the HPLP-II did not differ significantly by gender, but males scored better than females on the physical exercise subscale. Conclusions: This study suggest that university administrators, curriculum planners, community health professionals, and public health nurses may need to develop guidelines and interventions for structuring a healthier environment and developing health promotion programs to assist university students in developing healthy lifestyles.. Keywords: Health-Promoting Lifestyles; Jordan; University Students.